2022
DOI: 10.3389/fmicb.2022.858831
|View full text |Cite
|
Sign up to set email alerts
|

A Resistome Roadmap: From the Human Body to Pristine Environments

Abstract: A comprehensive characterization of the human body resistome [sets of antibiotic resistance genes (ARGs)] is yet to be done and paramount for addressing the antibiotic microbial resistance threat. Here, we study the resistome of 771 samples from five major body parts (skin, nares, vagina, gut, and oral cavity) of healthy subjects from the Human Microbiome Project (HMP) and addressed the potential dispersion of ARGs in pristine environments. A total of 28,714 ARGs belonging to 235 different ARG types were found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…From those contigs, ORFs were predicted using Prodigal (Hyatt et al, 2010 ). ARGs were annotated by comparing the ARG databases ARG_ANNOT (Gupta et al, 2014 ), RESFAMS (Gibson et al, 2015 ), and CARD (Jia et al, 2017 ) with both the assembled (ORFs) and unassembled (reads) data using blast (Maestre‐Carballa et al, 2019 , 2022 ). Only the best hits with a bit‐score ≥ 70, e‐value <10 −5 , and identities ≥50% or ≥ 90% (both thresholds were initially compared selecting later the cut‐off of ≥90% as likely the most reliable) were considered as potential ARG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From those contigs, ORFs were predicted using Prodigal (Hyatt et al, 2010 ). ARGs were annotated by comparing the ARG databases ARG_ANNOT (Gupta et al, 2014 ), RESFAMS (Gibson et al, 2015 ), and CARD (Jia et al, 2017 ) with both the assembled (ORFs) and unassembled (reads) data using blast (Maestre‐Carballa et al, 2019 , 2022 ). Only the best hits with a bit‐score ≥ 70, e‐value <10 −5 , and identities ≥50% or ≥ 90% (both thresholds were initially compared selecting later the cut‐off of ≥90% as likely the most reliable) were considered as potential ARG.…”
Section: Methodsmentioning
confidence: 99%
“…Only the best hits with a bit‐score ≥ 70, e‐value <10 −5 , and identities ≥50% or ≥ 90% (both thresholds were initially compared selecting later the cut‐off of ≥90% as likely the most reliable) were considered as potential ARG. The housekeeping genes present in the used ARGs databases were not considered in our metagenomic analysis due to the difficulty of determining if they were bona fide ARGs using our thresholds (Maestre‐Carballa et al, 2022 ) According to the database CARD (Jia et al, 2017 ) or the nr database (NCBI), the detected ARG were grouped by the antibiotic they confer resistance to. ARG abundance and normalisation were estimated by dividing the total number of ARGs per Gb of metagenome (assembled or unassembled) and if necessary, by volume sample as well.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that nares had the highest load of ARGs (~5.4 genes per genome), followed by the oral cavity, whereas the gut exhibited the lowest abundance (~1.3 genes per genome). Interestingly, the transfer of common ARGs from humans to pristine environments seemed to be very low or nonexistent [35]. The antibiotic resistome is dynamic and, at present, still expanding [16].…”
Section: The Antibiotic Resistomementioning
confidence: 99%
“…[ 55 ] in the vagina. Cabralla-Maestre and co-workers [ 56 ] reported that tetracycline resistance genes were the most frequent ARGs in the vagina of healthy non-pregnant women, followed by multidrug resistance genes. In comparison with the gut resistome, the vagina has a lower diversity in terms of antibiotic resistance [ 54 , 57 ].…”
Section: The Origin Of Infant Resistome: Vertical Transmission Of Argsmentioning
confidence: 99%